Cold-Tolerance Candidate Gene Identification in Maize Germination Using BSA, Transcriptome and Metabolome Profiling - Cheng Wang; Nan Hao; Yueming Li; Nan Sun; Liwei Wang; Yusheng Ye (Agronomy)
Exploring the characteristics of maize’s tolerance to low-temperature stress is of great significance for enhancing maize’s adaptability to such stress and for developing valuable germplasm resources. In this study, a combined analysis of genomics, transcriptomics, and metabolomics was conducted on maize 245 F7 recombinant inbred lines (RILs) to screen for candidate genes and differential metabolites controlling the cold tolerance of maize during the germination stage. Bulked segregant analysis-sequencing (BSA-seq) located four candidate regions on chromosome 1 (qSGRL1-2, qSGRL1-3, and qSGRL1-4) and chromosome 10 (qSGRL10), which altogether contained 109 candidate genes. Combined with the transcriptome sequencing results, among the genes screened by quantitative trait locus sequencing (QTL-seq), seven genes (Zm00001eb043000, Zm00001eb043620, Zm00001eb043650, Zm00001eb043680, Zm00001eb043720, Zm00001eb043400, and Zm00001eb043490) were identified as common candidate genes related to the cold tolerance of maize during the germination stage. Combined with the metabolomic analysis results, low-temperature stress induced the differential expression of relevant genes, leading to the differential accumulation of metabolites such as L-glutamic acid, 4-aminobutyric acid, and Lysophosphatidylcholine (LPC). These results enrich the information for molecular marker-assisted selection of maize tolerance to low-temperature stress and provide genetic resources for the maize varieties breeding.